2015
DOI: 10.1108/jfp-12-2014-0049
|View full text |Cite
|
Sign up to set email alerts
|

Structured community activity for forensic mental health – a feasibility study

Abstract: Purpose – The restrictive nature of low secure mental health settings and the issues associated with risk management and safe practice raise numerous challenges which need to be overcome for individuals to engage in community-based programmes. The paper aims to discuss these issues. Design/methodology/approach – Two community-based schemes are described. The first uses the natural environment as a medium in which to deliver opportunities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The affiliation domain findings support research which also shows that vocational construction training can encourage self-confidence, independence, social inclusion and create a sense of connectedness to the community [65,66]. It is widely recognised that homeless people's feelings of stigmatisation and isolation from mainstream society can undermine their pathways to employment [58] and researchers have also recognised the importance of positive social support mechanisms in securing and maintaining employment [67].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The affiliation domain findings support research which also shows that vocational construction training can encourage self-confidence, independence, social inclusion and create a sense of connectedness to the community [65,66]. It is widely recognised that homeless people's feelings of stigmatisation and isolation from mainstream society can undermine their pathways to employment [58] and researchers have also recognised the importance of positive social support mechanisms in securing and maintaining employment [67].…”
Section: Discussionsupporting
confidence: 58%
“…While our results only provided limited evidence that the outdoor nature of construction can strengthen connections with the natural world, it is notable that Nicholls [58] found the 'other species' component of Nussbaum's [40] framework to be of importance to homeless people and that other construction training programs for disadvantaged young people incorporated projects which included building bat boxes, ferret boxes and woodland projects [69]. Batterham [46] explains how homeless people can achieve a heightened sense of connection and belonging through interactions with nature and Roberts et al [65] found that construction training which used the natural environment as a medium to develop vocational skills reduced the depression and anxiety of participants. In Canada, there is also an innovative construction training program for homeless young people which focusses specifically on green jobs through projects such as energy conservation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence concerning less-secure settings is obtained from Roberts et al study [24], exploring two community-based schemes: one promoting vocational skills; the other, healthier living. The vocational project offered educative outdoor activities through a notfor-profit organisation, where accredited qualifications were awarded on completion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Davies et al, 2010) and has a history of development and innovation including the development of treatment programmes (e.g. Nagi et al, 2014) developing family involvement in low secure care (Nagi and Davies, 2015) and family liaison meetings in open rehabilitation (Davies, 2014) and utilizing community resources to support and foster inclusion (Roberts et al, 2015). These services have undergone significant redevelopment over the last two years; this process has caused us to reflect on our core values and recalibrate our "working compass".…”
Section: Introductionmentioning
confidence: 99%